GE_GERICHTE C/12108/2013 vom 25. September 2015 - GE Cour de justice (2015)
CONTRAT D'ENTREPRISE; PRIX FERME; COMPENSATION DE CRÉANCES; DÉFAUT DE LA CHOSE; RETARD; TRAVAIL SUPPLÉMENTAIRE | SIA.118; CO.42.2; CO.374